KOMUNIKASI EFEKTIF EDUKASI PASIEN BEDAH DI RS PKU MUHAMMADIYAH TEMANGGUNG - , EVI ALIFIA HARNANTI; , dr. Wahyudi Istiono, M.Kes. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: Patient education has many benefits, among others, so that patients and families to participate in treatment decisions and care process. Submission of a good patient education should be through effective communication between doctor and patient. Communication is done verbally and non-verbally generate an understanding of the patient's state of health, opportunities and constraints, so that doctors can jointly look for alternatives to overcome the problem. Based on preliminary studies obtained results that the provision of information in the informed consent sheet documented in Patient Education. According to interviews with medical records clerk, is often explained in the patient education sheet is not explained and the patient asked for a signature only. According to the results of quantitative analysis of the authentication not filled patient education sheet in column clinic is 20% while in the ward column was 50%. In addition to the patient education are also included in the 2012 Hospital Accreditation Standards Working Group Patient and Family Education Latest. Accreditation assessment that includes patient education suggests that patient education is one of the important material to support patient care and safety. Therefore, patient education should be considered. Goal: Knowing the communication between doctor and patient in the implementation of the provision of surgical patient education information. Method: This study used a qualitative descriptive method and case study research design. The subjects were 30 surgical patients who were treated by the same physician, a general surgeon, and general practitioner. While the object of this research is the implementation of the provision of patient education. Collecting data using observations, interviews and documentation studies. Samples were obtained using a purposive sampling. Result: Provision of medical information held in conjunction with the examination, the provision of administrative information held passively (when patients ask their doctor), and the provision of patient rights information only form of writing on the walls of the treatment room. Acceptance of most medical information is not received by the patient is KTD (Genesis Not Expected), most acceptance administrative information is not received by the patient is information about home plans, while for the receipt of information regarding patients' rights by the majority of patients more than 50% is not acceptable. The gap that occurs between giving and receiving the highest located on KTD (Genesis Not Expected).